2003
DOI: 10.1103/physrevb.68.054108
|View full text |Cite
|
Sign up to set email alerts
|

Local structure ofCuIn3Se5:X-ray absorption fine structure study and first-principles calculations

Abstract: A detailed extended x-ray absorption fine structure ͑EXAFS͒ study of CuInSe 2 and CuIn 3 Se 5 on Cu-K, InK , and Se-K edges was performed. It was found that CuInSe 2 and CuIn 3 Se 5 have well-defined local structure with the same average Cu-Se and In-Se bond lengths. They can be best described by structures containing weighted local tetrahedral cationic clusters around each Se: 2Cuϩ2In (kϭ8), and equal number of V Cu ϩCuϩ2In (k ϭ7) and V Cu ϩ3In (kϭ9), where k denotes the nominal number of valence electrons of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…In previous studies of ternary CuInSe 2 and quaternary Cu 2 ZnSnS 4 structures, the valence octet rule was found to play an important role in determining the energy stability of different structures. 7,25,29 The octet rule states that if the sum of the valence electrons of the cations surrounding the anion atom divided by the coordination number (four for tetrahedral structure) plus the number of the anion valence electrons is equal to eight, then the structure has low energy because the anion is in an eight-electron closed-shell state. For tetrahedral Cu 2 ZnSnS 4 , this requires the sum of the cation valence electrons surrounding each anion is equal 8 since S has 6 valence electrons.…”
Section: Crystal Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies of ternary CuInSe 2 and quaternary Cu 2 ZnSnS 4 structures, the valence octet rule was found to play an important role in determining the energy stability of different structures. 7,25,29 The octet rule states that if the sum of the valence electrons of the cations surrounding the anion atom divided by the coordination number (four for tetrahedral structure) plus the number of the anion valence electrons is equal to eight, then the structure has low energy because the anion is in an eight-electron closed-shell state. For tetrahedral Cu 2 ZnSnS 4 , this requires the sum of the cation valence electrons surrounding each anion is equal 8 since S has 6 valence electrons.…”
Section: Crystal Structuresmentioning
confidence: 99%
“…The situation is similar to the CuInSe 2 -derived ordered vacancy compounds. 29 Ordered vacancy compounds are formed by creating ordered (In Cu + 2V Cu ) defect pairs in CuInSe 2 , 30 whereas Cu 2 SnS 3 can be considered as formed by creating ordered (Sn Zn + 2Cu Zn ) defect pairs in Cu 2 ZnSnS 4 .…”
Section: Crystal Structuresmentioning
confidence: 99%
“…Experimentally, the structure of the commonly observed Cu deficient phase CuIn 3 Se 5 has been interpreted in terms of several quite different structural models, 28 with no consensus. However, some theoretical models have been proposed to investigate this phase.…”
Section: Resultsmentioning
confidence: 99%
“…Density functional theory (DFT) 25,26 methods of QM are widely used to investigate the relationship between chemistry and functionality of materials, and some DFT efforts have previously been applied toward such aspects of CIGS solar cells, as defect formation 19,[27][28][29][30][31][32] and levels. [33][34][35] The most important aspect of CIGS solar cells is the CIGS/CdS interface, where the essential physics of photovoltaics takes place.…”
Section: Introductionmentioning
confidence: 99%
“…First-principles calculations demonstrated that the total energies of all these models are extremely close: the difference between them not exceeding 4 meV/atom. 6 This explains why the long-period ordering of defects/vacancies cannot be determined experimentally without ambiguity. The structure of CuIn 3 Se 5 depends considerably on the crystal growth conditions and annealing history.…”
mentioning
confidence: 99%